The World's Best-kept Beauty Secrets : Hundreds of Insider Tips from the Worlds of Beauty, Diet and Fashion - Irons, Diane, 1949- (London Vermilion, 1997)
Revealing hundred of insider tips on how to look and feel fabulous, inside and out, this text is written by a former model and confidante to the stars. Diane Irons demystifies the hype surrounding the costly products and fads of the beauty industry so that you can energize your own style.
Include Index
Keywords: Beauty, Personal -- Beauty Secrets